O pensar da elite sobre o povo comum: espaço público, viver urbano e reterritorialização do centro da cidade de Campo Grande (décadas de 1960-70) - Moro, Nataniél Dal (2012)
This thesis analyzes how a part of the ruling elite of the city of Campo Grande conceived the presence of commoners, humble workers, beggars, prostitutes, milkmen, hikers, and a wide range of other poor people that was visible in the city centre, especially in public spaces. This work also investigates other issues, namely: 1) how certain douments produced by memorialist authors contributed to build a glorious past about pioneers and their achievements; 2°) elite s and common people s practices in the city are shown; 3) conflicts between elite and common people in the city area are identified and 4) it is demonstrated that the printed mass state media Correio do Estado served as a political party, advocating the existence of a civilized, modern and orderly city compared with the ways of living of other individuals, especially those by the common people. Most of the sources was collected in the following places: Historic Archive of Campo Grande, the Municipal Chamber of Councillors of Campo Grande, Instituto Histórico e Geográfico de Mato Grosso do Sul, Fundação Barbosa Rodrigues, Fundação Instituto Brasileiro de Geografia e Estatística and, above all, the Archives of Correio do Estado newspaper. They are documents and images produced by these institutions and by various associations, institutes, departments and civil people. Stories of several approaches, maps, informative advertising, photographic images, chronicles, official publications, such as laws, codes, ordinances and resolutions, in addition to letters published by public and private organs and authorities, among others, which also make part of the list of sources. The writings of Karl Marx, Walter Benjamin, Antonio Gramsci, Eric Hobsbawm, E. P. Thompson, Raymond Williams and Pierre Bourdieu have been fundamental to problematize these sources. The Correio do Estado (CE) showed masterfully in its pages the urban life and city in transformation. Exposed a confrontational dialogue between public authorities and the society at large. The CE also showed with richness of details the tendentiousness of the media, with emphasis on the partisan nature in favor of one or another goal. At this time, the CE has proved to be a real political party, since it has met the desires of some groups, arguably more of the local elite of that of ordinary people, and denied the interest of many other individuals. However, when the CE described and analyzed the city, it did not show the city itself in all its forms and essences, but much more, its conception of the world about the city and the values it espoused. Therefore, the material published in the journal don't show exactly the history of Campo Grande city, neither the history of the individuals that were in it, but, above all, the history of the performance of this media as a political agent who represented certain groups and social values and acted in several ways regarding the city and the population of Campo Grande, much more with the goal of defending the interests of the groups that the journal represented than any other purposes